Pseudorapidity distributions of charged particles as a function of mid- and forward rapidity multiplicities in pp collisions at √s = 5.02, 7 and 13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Agha, S.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; et al. (Springer Science and Business Media Deutschland GmbH, 2021)
The multiplicity dependence of the pseudorapidity density of charged particles in proton–proton (pp) collisions at centre-of-mass energies √s = 5.02 , 7 and 13 TeV measured by ALICE is reported. The analysis relies on track segments measured in the midrapidity range (|η| < 1.5 ). Results are presented for inelastic events having at least one charged particle produced in the pseudorapidity interval |η| < 1. The multiplicity dependence of the pseudorapidity density of charged particles is measured with mid- and forward rapidity multiplicity estimators, the latter being less affected by autocorrelations. A detailed comparison with predictions from the PYTHIA 8 and EPOS LHC event generators is also presented. The results can be used to constrain models for particle production as a function of multiplicity in pp collisions.
Keywords: Pseudorapidity; Rapidity; Multiplicity (mathematics); Physics; Charged particle; Nuclear physics; Large Hadron Collider; Particle physics; Range (aeronautics); Proton; Ion; Geometry; Mathematics; https://purl.org/pe-repo/ocde/ford#1.03.00